Population demography of Peary caribou and muskox on Banks Island, N.W.T., 1982-1992 - Nagy, J.A.; Larter, N.C.; Fraser, V.P. (Rangifer, 1996)
The Peary caribou population (excluding calves) on Banks Island declined from 6 970 (± 1133) in 1982 to 897 (± 151) in 1991. The 1992 estimate was 1 005 (± 133). Percent calves in the population varied among years (range 3.2¬31.1%). Mean group sizes dropped from 5.0 in 1985 to a low of 2.0 in 1989 and 1991. Median group sizes were significantly larger between 1982 and 1987 than between 1989 and 1992 (P<0.001). Large post-calving aggregations prevalent on the NW portion of Banks Island in the early 1980's were absent by the 1990s. The muskox population (excluding calves), increased from 29 168 (± 2104) in 1985 to 52 959 (± 2240) in 1992. Percent calves in the population varied among years, (range 11.8-17.1%). These values may be underestimates, because calves are small and muskox groups sometimes form defensive circles in response to aircraft. Muskoxen were distributed throughout the island during all surveys; however, the greatest increase in density occurred in the southern parts of the island.